2011
DOI: 10.2135/cropsci2011.02.0112
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of QTL Reducing Aflatoxin in Maize Testcrosses

Abstract: Aflatoxins, produced by the fungus Aspergillus flavus Link:Fr, constrain maize (Zea mays) production in some regions. Difficulties in breeding resistance to this toxin make it a good target for quantitative trait iocus (QTL) identification and molecular-assisted breeding. Multiple QTL have been identified for aflatoxin resistance in inbred lines per se; however, it has not been determined if aflatoxin resistance QTL would be useful in hybrids or have deleterious pleiotropic effects. The objectives were to conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 36 publications
1
20
2
Order By: Relevance
“…Testcross progenies show reduced variation for a trait because of the contribution of only one allele from the corresponding RIL population. The QTLs detected in the RIL testcrosses are different from the RILs due to dominance effect of the heterozygous loci as well as epistasis between locus and genetic background ( Jines et al, 2007;Kerns et al, 1999;Mayfield et al, 2011). Several QTLs reported in the study are unique to the study and the QTLs that coincided with earlier studies were described.…”
Section: Locationmentioning
confidence: 62%
“…Testcross progenies show reduced variation for a trait because of the contribution of only one allele from the corresponding RIL population. The QTLs detected in the RIL testcrosses are different from the RILs due to dominance effect of the heterozygous loci as well as epistasis between locus and genetic background ( Jines et al, 2007;Kerns et al, 1999;Mayfield et al, 2011). Several QTLs reported in the study are unique to the study and the QTLs that coincided with earlier studies were described.…”
Section: Locationmentioning
confidence: 62%
“…Eight QTL mapping experiments on A. flavus or aflatoxin resistance [35][36][37][38][39][40][41][42] and one additional on ear rot due to A. flavus [43] have been published to date. Most of these QTL studies have reported multiple QTL, most of which have been found in only one environment, and the majority of the QTL each account for less than 5% of the phenotypic variation observed in the population and the environment in which it was measured.…”
Section: Mapped Aflatoxin Resistance Qtlmentioning
confidence: 99%
“…Ear rot was the subject of a recent meta-analysis (Xiang et al, 2010), but the study did not include data for resistance to mycotoxin accumulation, and we are not aware of prior studies reporting meta-analysis of aflatoxin resistance. With the recent publication of three new QTL mapping studies on resistance to aflatoxin accumulation and an additional study presented here, the number of available studies has increased, making a metaanalysis of this trait more relevant (Mayfield et al, 2011;Warburton et al, 2010;Willcox et al, 2013).…”
Section: Fungal Isolate Inoculation Procedures and Phenotypingmentioning
confidence: 99%
“…The largest of these (representing the most QTL) was mqtl5 on chromosome 4, which was formed by four QTL for resistance to aflatoxin accumulation (Supplemental Table S3). These included qbAFL4.08, located near marker PHM3637 in maize bin 4.08 in our stepwise regression analysis, and QTL from populations Mp313E × B73 (Brooks et al, 2005), B73O2/O2 × CML616 (Mayfield et al, 2011), and Mp313E × Va35 (Willcox et al, 2013).…”
Section: Quantitative Trait Loci Meta-analysismentioning
confidence: 99%